2016
DOI: 10.1016/j.apsusc.2016.06.059
|View full text |Cite
|
Sign up to set email alerts
|

Microchannel fabrication on cyclic olefin polymer substrates via 1064 nm Nd:YAG laser ablation

Abstract: This paper presents a method for fabrication of microchannels on cyclic olefin polymer films that have application in the field of microfluidics and chemical sensing. Continuous microchannels were fabricated on 188-µm-thick cyclic olefin polymer substrates using a picosecond pulsed 1064 nm Nd:YAG laser. The effect of laser fluence on the microchannel morphology and dimensions was analysed via scanning electron microscopy and optical profilometry. Single laser passes were found to produce v-shaped microchannels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 29 publications
(35 reference statements)
3
25
1
Order By: Relevance
“…Though some reduction in peak intensity was evident, this was attributed to the deposited gold film reducing the sampling depth into the COP bulk. Though no significant degradation was seen over the range of fluences examined in this work, previous studies have demonstrated substrate melting at fluences of 0.34 J/cm 2 and substrate warping at fluences of 0.79 J/cm 2 [23]. Neither warping or melting was evident from the morphological examination, however it is possible that damage may become evident if a larger laser fluence range is examined.…”
Section: Surface Chemistrycontrasting
confidence: 56%
See 1 more Smart Citation
“…Though some reduction in peak intensity was evident, this was attributed to the deposited gold film reducing the sampling depth into the COP bulk. Though no significant degradation was seen over the range of fluences examined in this work, previous studies have demonstrated substrate melting at fluences of 0.34 J/cm 2 and substrate warping at fluences of 0.79 J/cm 2 [23]. Neither warping or melting was evident from the morphological examination, however it is possible that damage may become evident if a larger laser fluence range is examined.…”
Section: Surface Chemistrycontrasting
confidence: 56%
“…Previous work on the thermal degradation of COC has seen the formation of spectral features such as increased C=O stretching at 1710 cm -1 , C=H stretching (2900 -2800 cm -1 ) and the formation of a large band at 4000 -3000 cm -1 (indicative of C=C-H) [22,23]. As the C=H and C=O bonds are at similar intensities before and after deposition, there has been limited oxidation and dehydrogenation of the surface due to the laser deposition process.…”
Section: Surface Chemistrymentioning
confidence: 99%
“…† Our group was the rst to report the fabrication of patterned structures on optically transparent 188 mm thin COP lm via a simple laser assisted technique in ambient atmosphere without the need of controlled gas chambers. 24 This technique offers a low cost, innovative and exible route to fabricate different patterns with varied features (size, shape, morphology, etc.) by tuning laser parameters (such as laser uence and number of passes).…”
Section: Substrate Processing and Characterizationmentioning
confidence: 99%
“…To realize the application of these generated substrates in a lab-on-a-chip/biosensor format, several test experiments (not reported here) were performed to optimize the generated pattern. 24 The principal criteria taken into consideration were the wettability, roughness, reproducibility and ease of functionalization. With these in mind, the fabrication routine was nalized.…”
Section: Substrate Processing and Characterizationmentioning
confidence: 99%
“…Biofabrication techniques of polymeric devices and hydrogels through laser technology have been reported [27,28], and their viability for producing 2-D and 3-D grafts is remarkable [28,29]. However, some of the processing methods have high operating cost, such as UV and femtosecond lasers [30], or only works with transparent materials, as a tightly focused ultrafast laser beam at infrared wavelength [29]. Extreme ultraviolet laser might change the degradation rate of the polymeric biomaterial [31], and some techniques, such as the matrix-assisted pulsed laser evaporation direct writing (MAPLE-DW), imply in using metallic layers that might contaminate the final product [28].…”
Section: Introductionmentioning
confidence: 99%